Emfisema Subkutis sebagai Komplikasi pada Pasien Covid-19 dengan Penggunaan Ventilasi Mekanik - Panduwaty, Lira; Trilaksmi, Antin; Cipta, Ferdy (Sanus Medical Journal, 2022)
Background. The incidence of subcutaneous emphysema in patients with severe pneumonia caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus infection has been in the spotlight recently. Subcutaneous emphysema is a rare complication. With the increasing prevalence of subcutaneous emphysema in patients with confirmed coronavirus disease (COVID-19), it is necessary to know what factors can cause this and how to treat it. Case Description. Two patients, a man and a woman aged 50 and 70 years, diagnosed with COVID-19, came to the Emergency Room (IGD) of Bunda Menteng General Hospital, Jakarta, with symptoms of acute respiratory distress syndrome (ARDS). Both patients experienced severe shortness of breath with a respiratory rate above 30 times per minute. Then the two patients were treated in the intensive care Unit (ICU) isolation room and required mechanical ventilation assistance. After 3-4 days of mechanical ventilation treatment, subcutaneous emphysema develops, characterized by subcutaneous crepitus. After chest x-rays were carried out in both patients, the results were subcutaneous emphysema and pneumomediastinum. Several invasive procedures have been performed, such as subcutaneous insertion of an intravenous cannula, mediastinoscopy, and chest tube insertion. Conclusion. Complications of subcutaneous emphysema in COVID-19 patients are rare and require further research to determine the cause, where the infection is still the focus. With this case report, it is hoped that clinicians will pay more attention to the initial clinical findings of subcutaneous emphysema to reduce even more severe complications such as pneumothorax.